216k views
0 votes
Can someone help me with these first 2

Can someone help me with these first 2-example-1

1 Answer

7 votes

Answer:

Explanation:

So the two have different strategies, I'll try and explain both.

The first you work backwards in a way, where if you want to find the, say, fourth, you need the third, and for that you need the second, and so on. What the function is saying specifically is, the nth term is going to be the square root of the term before that one, or the " n minus one-th". Luckily it wants you to go in order from the first to fourth, so we can just go in order.

It also does tell us the first term. so f(1).

f(1) = 65,536

f(2) = sqrt(f(2-1)) = sqrt(f(1)) = sqrt(65,536) = 256

f(3) = sqrt(f(3-1)) = sqrt(f(2)) = 16

Now an you find the fourth and final term you need? if not I can walk you through it.

For the second one you just have to plug in. it's basically a normal function. if you wanted to find the 100th term you just plug it in for n. so f(100) = 100^3-1 = 1,000,000 - 1 = 999,999. All you want is f(1), f(2), f(3) and f(4). I will leave the first three to you unless you don't get it, but to show you how I will do the fourth really quick. the fourth is f(4) which is 4^3 - 1 = 64 - 1 = 63.

Again, let me know if you need further help.

User Alecxs
by
5.9k points